Hormander's Inequality for Anisotropic Pseudo-dierential Operators (Journal of Partial Differential Equations, 2020)
We prove a generalization of Hörmander's celebrated inequality for a class of pseudo-differential operators on foliated manifolds.
Keywords: Pseudo-differential operators; lower bounds; inequalities